Relationship between green information technology practices and attitudes of student in School of Technology Management and Logistics, Universiti Utara Malaysia - Lim, Chew Bei; Ibrahim, Jafni Azhan (2017)
Green Information Technology is a study and practices of environmentally sustainable Information Technology.The lack practice of green information technology is the one issues of green information technology.When Information Technology sector growing rapidly become a problem of increasing energy waste, paper waste and electronic waste.For this research will be focused on the relationship between green information technology practices and student’s attitudes. This research to evaluate the practices of green information technology and to analyse the student’s attitudes of the practices of green information technology.Then to determine the relationship between green information technology practices and student’s attitudes. After that to encourage the green information technology practices.This study used questionnaire survey to collect data from Universiti Utara Malaysia students. Using statistics to analyse the correlation and regression analysis, there is a positive relationship between green information technology practices and student’s attitudes. In general, it can be concluded that students should be aware and practices of green information technology, but must practices on good behaviour. With the aim of getting more accurate result, except collect data from students, also should be collect data from other people in society.